2009
DOI: 10.1111/j.1365-2567.2008.02948.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial lipopeptide triggers massive albuminuria in murine lupus nephritis by activating Toll‐like receptor 2 at the glomerular filtration barrier

Abstract: Summary What are the molecular mechanisms of bacterial infections triggering or modulating lupus nephritis? In nephritic MRLlpr/lpr mice, transient exposure to bacterial cell wall components such as lipopeptide or lipopolysaccharide (LPS) increased splenomegaly, the production of DNA autoantibodies, and serum interleukin (IL)‐6, IL‐12 and tumour necrosis factor (TNF) levels, and aggravated lupus nephritis. Remarkably, bacterial lipopeptide induced massive albuminuria in nephritic but not in non‐nephritic mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 43 publications
0
54
0
Order By: Relevance
“…More recently other investigators have detected protein with immunohistochemical staining for TLR4 reported to be on podocytes in normal mouse glomeruli. 21 Murine glomerular endothelial cells and podocytes both express TLR4, 22 and cultured podocytes have been shown to express TLR4 and to undergo phenotypic changes including cytoskeletal reorganization and B7.1 expression in response to TLR4 stimulation. 23 A further report demonstrated that podocytes express a range of chemokines in response to TLR4 stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…More recently other investigators have detected protein with immunohistochemical staining for TLR4 reported to be on podocytes in normal mouse glomeruli. 21 Murine glomerular endothelial cells and podocytes both express TLR4, 22 and cultured podocytes have been shown to express TLR4 and to undergo phenotypic changes including cytoskeletal reorganization and B7.1 expression in response to TLR4 stimulation. 23 A further report demonstrated that podocytes express a range of chemokines in response to TLR4 stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…LPS priming was required for severe tissue damage, probably because LPS induced TLR2 and TLR4 inside the kidney, consistent with previous reports on endothelial and tubular epithelial cells. [28][29][30] In fact, lack of TLR2/4 partially prevented renal necrosis after histone injection. We admit that histones were injected at high concentrations in these experiments, which may not mimic the physiologic situation.…”
Section: Discussionmentioning
confidence: 99%
“…TLR2 and TLR4 are both expressed on intrarenal immune cells as well as on renal parenchymal cells. [6][7][8]28,29 Studies with TLR2/TLR4 bone marrow chimeric mice revealed that postischemic danger signaling via TLR2/TLR4 dominates in renal parenchymal cells. 6,8 The fact that histone neutralization protected distal but not proximal tubular epithelial cells in the postischemic kidney should relate to the fact that only distal tubular cells upregulate TLR2 and TLR4 in the postischemic kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Wolfs and colleagues showed that TLR2 are constitutively expressed on the renal epithelial cells of distal and proximal tubules, the epithelium of Bowman's capsule, glomerular and endothelial cells in the I/R model kidney. 18 Pawar et al 22 found that bacterial lipopeptide activated TLR2 expressed on cultured podocytes and glomerular endothelial cells in vitro. In our current study, we demonstrated that TLR2 was also overactivated in two non-immune cell types, podocytes and glomerular endothelium cells, in vivo using a LPS-induced AKI model.…”
Section: Discussionmentioning
confidence: 99%